2015
DOI: 10.1021/jf5050734
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-SPE-NMR Characterization of Major Metabolites in Salvia fruticosa Mill. Extract with Antifungal Potential: Relevance of Carnosic Acid, Carnosol, and Hispidulin

Abstract: Plant pathogenic fungi are considered of significant economic importance for adversely affecting both quantitatively and qualitatively fresh and processed produce. Extracts of Salvia fruticosa were initially screened for their antifungal activity, and the ethyl acetate fraction, being the most active, was further analyzed using HPLC-SPE-NMR hyphenation. The methoxylated flavones hispidulin, salvigenin, and cirsimaritin and the diterpenes carnosic acid, carnosol, and 12-methoxycarnosic acid were identified as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 52 publications
3
40
0
3
Order By: Relevance
“…In particular, these phytochemicals were attributed to carnosol, carnosic acid and 12‐methoxy carnosic acid. The identification of six phytochemicals was described in detail in our previous work . NMR data for all identified compounds are provided in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, these phytochemicals were attributed to carnosol, carnosic acid and 12‐methoxy carnosic acid. The identification of six phytochemicals was described in detail in our previous work . NMR data for all identified compounds are provided in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, quantitative NMR (q‐NMR) was used to quantify the major phytochemicals (Supporting Information 1). HPLC‐SPE‐NMR and q‐NMR methods were described in a previous work …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1) that has been identified as the major bioactive phytochemical in numerous medicinal plants, including Rosmarinus officinalis (8), Salvia fruticosa (9) and Ocimum sanctum (10). Previous pharmacological studies have demonstrated that carnosic acid affords various biological activities, such as neuroprotection (11), prevention of advanced glycation end-product formation (12), attenuation of Alzheimer's disease (13), anticancer activity (14), anti-inflammation (15) and renoprotection (16).…”
Section: Introductionmentioning
confidence: 99%